Understanding and coping with foreign language anxiety - Paniagua Camacho, María José (2022)
Foreign Language Anxiety or FLA has become one of the most constant and persistent issues to be faced in the English classroom; thus, FLA is currently a complex obstacle for students to achieve a meaningful learning experience. Research has shown how students who undergo FLA are able to understand what they are doing in the classroom; nevertheless, “understanding” a topic or activity in class does not equate to going through a significant learning process. Considering the effect FLA can have in the students’ learning experience in addition to the rise in the public’s interest for concepts such as “mental health” and “anxiety” in recent years, it is of uttermost importance for teachers to be up-to-date with regard to this issue. This paper is based on current literature about the meaning behind FLA, its causes, its effects, and coping strategies for it. The analysis of the literature demonstrated all EFL students can experience FLA if one or more factors intertwine and trigger a crisis. This is because age, gender, proficiency, or emotional intelligence level do not contribute to a learner undergoing FLA. Moreover, it was clear that learning about the causes of FLA is the first step for an educator to create an anxiety-free classroom. Getting to know the triggering factors can not only help a teacher identify anxious students, but also inspire them to question their own pedagogical praxis. Finally, it is important to highlight that the inquiry indicated the relevancy of teachers instructing students on coping strategies for FLA since this can make a difference not only in class but in the learner’s life